Comparison of Herbal and Non-Herbal Dental Pasta Effectiveness Towards Children's Dental Plaque Index - Jeffrey .; Marlin Himawati (Maranatha Christian University, 2021)
Abstract Dental plaque is formed from biofilm that coats the surface of the teeth and is an indicator of dental and oral hygiene. One way to control plaque is by brushing your teeth. Herbal toothpaste is expected to inhibit plaque growth because it is related to the ability of herbal ingredients to inhibit microbial growth. This study aims to determine the comparison of the effectiveness of herbal and non-herbal toothpaste on reducing the plaque index in children aged 15-18 years (WHO). This type of research is experimental with pretest-postest group design on 30 respondents obtained by total sampling method and divided into 2 groups. A total of 15 respondents in the first group used herbal toothpaste and 15 respondents in the second group used non-herbal toothpaste. The plaque index is measured based on the Loe and Silness plaque index. Paired t test was used to determine the difference in dental plaque index before and after treatment. The results showed that there were significant differences in the dental plaque index on the use of herbal and non-herbal toothpaste for children aged 15-18 years. Keywords: plaque index, herbal toothpaste, non herbal toothpaste